The algorithm of interpolating windowed FFT for harmonic analysis of electric power system. - Fusheng Zhang (IEEE Transactions on power delivery)
The fast Fourier transform (FFT) cannot be directly used in the harmonic analysis of an electric power system because of its higher errors, especially the phase error. This paper discusses the leakage phenomenon of FFT and presents a new amending algorithm, poly-item cosine window interpolation, which is based on the interpolating algorithm proposed by V. Jain and T Grandke. This new algorithm improves the accuracy of the FFT, so it can be applied to the precision analysis for electrical harmonics. The simulation result shows that applying different windows has different effects on the accuracy, and the Blackman-Harris window has the highest accuracy